Notranji kanali za prijave in minimalni standardi za zaščito prijaviteljev - Jasnič, Dejan (Podjetje in delo, 2020)
The paper addresses the provisions of the Directive on the protection of persons who report breaches of Union law concerning the establishment of internal reporting channels, the conditions for the protection of reporting persons against retaliation and protection measures. The required establishment of internal reporting channels in the private and public sectors is a welcome development in the field of compliance and integrity in the EU. The paper presents which legal entities are obliged to establish internal reporting channels, to whom they should be accessible, what are the requirements for protecting confidentiality and allowing anonymous reports, what procedures should be defined, and what feedback should be given to the reporting person and within what deadlines. Special attention is paid to the provisions defining the conditions for the protection of reporting persons. Retaliation occurs in practice in many forms and poses a high risk to any reporting person. The Directive broadly defines its personal scope, highlights the importance of informing the public about the procedures and their rights and, considering the weaker position of the reporting person in proving retaliatory measures, reverses the burden of proof. For more effective protection against retaliation, it is essential that national legislations define the conditions for such protection more favourably to the reporting persons than those set out in the directive. According to the latter, the bar is set quite high, which provides protection to a fairly narrow circle of reporting persons, which does not exclude only malicious reporting persons. The burden of proving that the required conditions are met will represent too high a risk for many potential reporting persons.
Keywords: bona fide reporting; Directive on the protection of persons reporting on breaches of Union law; Direktiva o zaščiti oseb, ki prijavijo kršitve prava Unije; dobrovernost prijaviteljev; good faith reporting; povračilni ukrepi; prijavitelji; protection of whistleblowers; retaliatory measures; whistleblowers; whistleblowing; zaščita prijaviteljev; žvižgaštvo